In vitro anti-inflammatory, antidiabetic, antibacterial, and in silico studies of Ferruginan A isolated from Olea ferruginea Royle (Oleaceae) - Abdur Rauf; Bassam Oudh Aljohny; Umer Rashid; Yasir Anwar; Zafar Ali Shah; Naveed Muhammad; Anees Ahmed Khalil; Ahood Khalid; Gauhar Rehman (Elsevier, 2023)
Objective: Traditionally, Olea ferruginea Royle (Oleaceae) has been used as a painkiller and antidiabetic in various ailments. To provide a scientific background to this folklore the current study was designed to anti-inflammatory and antidiabetic effects of one of the isolated compound from this plant. Methods: Ferruginan A was isolated from the ethyl acetate extract of Olea ferruginea bark. This isolated molecule was subjected to in-vitro anti-inflammatory and antidiabetic effects using HRBCs and glucose uptake tests. The compound was also tested for molecular docking and ADMET study. Results: Regarding the anti-inflammatory effect, the tested compound demonstrated a 69.82 % inhibition at a concentration of 100 µg/mL, while the Ferruginan A (100 µl/mL) increased the uptake of glucose (3.79-71.86 %) in the yeast cell. Similarly, the zone of inhibition values of Ferruginan A (24.98 mm) against Escherichia coli were found to be comparable to standard (Imipenem: 31.09 mm). The mechanism of antidiabetic and anti-inflammatory effects was explored by using docking simulations performed on four molecular targets related to diabetes and inflammation. The results showed that the isolated compound may act as an antidiabetic agent by inhibiting the 5' Adenosine monophosphate-activated protein kinase (AMPK). While it also showed inhibition of anti-inflammatory targets COX-1, COX-2, and Tumor necrosis factor alpha (TNF-α). The ADMET prediction study revealed that isolated compound possesses favorable ADMET profile. Conclusion: It was concluded that Ferruginan A might be a significant anti-inflammatory and antidiabetic molecule.